PROBLEMS OF RUSSIAN BUSINESS INTEGRATION INTO THE GLOBAL MARKET OF INFORMATION TECHNOLOGIES - A. Krylosov (Вестник университета)
The article discusses the main challenges and prospects of Russian companies’ integration into the world market of information technologies in the context of political uncertainty in relations with western countries. The author outlines the internal problems of the Russian sector of information technologies associated with low demand in software development, unfair competition in the information technologies market.